Pengaruh Proses dan Penerapan Disiplin Terhadap Spiritual Anggota Gereja Masehi Advent Hari Ketujuh di Jemaat Pioneer Amurang Berdasarkan Matius 18:15-17 - Tumonggor, Hendrikus Vendy; Pardosi, Milthon Thorman (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study examines the perceptions of members of the Pioneer Amurang Seventh-day Adventist Church regarding the process and application of discipline within the church, grounded in Jesus' teachings in Matthew 18:15–17. The primary objective is to analyze the extent to which understanding and applying discipline influences the spirituality of congregation members in embodying the values of the Kingdom of God through various religious activities.Using descriptive analysis and causal relationship testing, this study investigates the relationship between the independent variables (the process and application of discipline) and the spirituality of church members, based on actual population data. The findings indicate that the application of discipline has a positive and significant impact on members' spirituality. When discipline is applied in accordance with biblical principles, it encourages congregation members to be more obedient and faithful in worship.Moreover, disciplinary decisions are well-received when the process and implementation align with the teachings of Matthew 18:15–17, ultimately strengthening members' spirituality. The understanding of Matthew 18:15–17 serves as a moderating variable, reinforcing the influence of discipline on religious practice. This scriptural guideline helps congregation members align their material and social lives with Christian values. The study highlights the importance of discipline's process and application in the church to foster members' spirituality towards God.